Guest Satisfaction to Stay in The Hotel Industry: The Antecedent Factors Investigation - Saputra, Panji; Dortina Hutabarat, Ruth Sama; Ferdian, Feri (Jurnal Manajemen Pelayanan Hotel, 2023)
Customer satisfaction is the level of customer satisfaction, desire, or positive perception of the product, service, or experience they receive. This reflects the extent to which customers are satisfied with the product or service they purchased. The purpose of this study was to examine the effect of service quality on customer satisfaction in the hotel non-star Padang mediated by ambient conditions. This study used quantitative research with a causal associative approach. Data was obtained by distributing questionnaires directly to guests staying in the hotel non-star Padang so that a total sample of 112 respondents from a population of 7 in the hotel non-star Padang were obtained with a Likert scale. The data analysis technique uses Partial Least Square Structural Equation Modeling. Most of the respondents are between 21-30 years old. with 60.71% of respondents. This study found that service quality is an important factor in increasing ambient conditions and customer satisfaction in the hotel non-star Padang. Meanwhile, ambient conditions did not affect customer satisfaction in the hotel non-star Padang. Although service quality is an important factor in customer satisfaction, the results of the analysis show that ambient conditions as mediated factors do not have an effect on service quality and customer satisfaction in the hotel non-star Padang. Keywords: Service Quality, Ambient Condition, Customer Satisfaction